New post graduate students' orientation programme - Mathew, Vloreen Nity (UiTM Sarawak, 2015)
On 13th September 2014, the Centre of Graduate Studies, UiTM Sarawak organized an orientation programme to welcome all new students for the September 2014 intake. The programme was held at the Grand Margarita Hotel, Kuching. 22 new students for research and coursework programmes turned up to register for the upcoming new semester. The programme, which started with a networking lunch, gave an opportunity for the new students, coordinators and the Post Graduate Centre staff to get to know each other. Registration took place at about 2 pm and students were sent to attend a programme briefing by the respective coordinators for research and coursework. The Research Programme briefing was conducted by Dr Corina Joseph while programme briefings for coursework were conducted by Siti Huzaimah and Vloreen Nity Mathew. The briefing highlighted Important dates and requirements for students to complete the programme. The programme ended at 6.00 p.m. with a message from the Head of Post Graduate Centre, Associate Professor Dr. Firdaus Abdullah.